CHITRA BANERJEE DIVAKARUNI’S SISTER OF MY HEART – A WOMAN’S CULTURAL TRAUMATIC EXPERIENCE (Forum for Linguistic Studies, 2024)
Chitra Banerjee Divakaruni is a diasporic writer whose novels depict not just the cross-cultural conflicts but also the emergence of a new class of women who stand apart in fighting against the oppressive Indian tradition and social dogmas humiliating women.  The latter theme is the premise of the novel Sister of My Heart.  Her meticulous efforts spread before the readers the acute sufferings of women in a male chauvinistic and socially regressive society.  In an era with its strong revolutionary ideas uplifting the status of women, the novelist attempts to showcase how women disentangle themselves from the clutches of the constricting norms.  This paper envisages to project a dimensional approach in exposing the two generations of women who, in their ground-breaking conduct, dislodge the misguided and belittling familial and social life. In the process, two significant aspects stand out prominently.  The elder women as mothers and the younger ones as sisters bond so resourcefully that their lives metamorphose into a rationally different one for the better.